Human exposure to airborne particles during wood processing. (November 2018) - Gu, Jianwei; Kirsch, Ina; Schripp, Tobias; Froning-Ponndorf, Frank; Berthold, Dirk; Salthammer, Tunga
Abstract: Wood processing has been known to emit a large amount of inhalable wood dust, but the emissions of particles with diameters smaller than 10 μm and ultrafine particles (UFP, particles with diameters smaller than 100 nm), as well as their exposure levels, remain unclear. The present study measured the particle profiles from 5.6 nm to 10 μm from wood processing in a pilot plant and in the wood industry, respectively. Large increase of particle number concentrations (PNC) was observed during pilot scale refinery, flaking, cross hammer mill, chipping and sawing, but not during sieving, drying, gluing and pressing, when comparing with background PNC. In the wood industry (one sawmill and one wood-based panel factory), we observed high PNCs, and in some production sites (chipping, MDF form station, MDF press station) high particle mass concentrations (PMCs). Human respiratory tract deposition modelling showed that the deposition of the particle surface area in the size range of 0.3–10 μm was mainly in the extrathoracic region, and the particle surface area in the size range of 5.6–560 nm was mainly deposited in the alveolar interstitial. Exposure of a few minutes when processing wood in the pilot plant can lead to a high particle dose. The particle dose for an 8-h exposure in the wood industry was much higher than urban background exposure scenarios, in some workplaces by a factor of about 50–100. This study gives first evidence that wood processing could emit a large number of UPF and particles <10 μm. Our results indicate that the current mass-based occupational exposure limit for wood dust is not able to reveal the high exposure to UFP and particles <10 μm. Highlights: UFP and particles <10 μm measured during wood processing and in the wood industry. High UFP number concentrations observed for several wood processing activities. Particle size profiles obtained for a variety of wood processing activities. Exposure to wood processing leads to high particle dose in the sub-10 μm size range.